Потенциальные возможности использования и особенности применения нанотехнологий в производстве современных строительных материалов - Пентюк, Б. Н.; Човнюк, Ю. В. (НТУ "ХПИ", 2007)
Розглянуті особливості нанотехнологій стосовно до потреб будівельної індустрії. Зокрема, визначені потенційні можливості використання нанотехнологій активування води, наноарматури та подрібнення вихідних матеріалів з метою покращення показників виробництва та властивостей будівельних матеріалів.

The characteristic properties of nanotechnologies due to building industry’s necessities are discussed. One may determine the potential possibilities of using of nanotechnologies just for water’s activation, nanoreinforcement and comminution of starting materials as well. Such approach gives the possibilities to improve the industrial indicators of production and properties of the building materials as well.
Keywords: нанохимия; наночастицы; структурные элементы; нанокомпозиты; порошковые материалы